Treatment outcomes for patients with Middle Eastern Respiratory Syndrome Coronavirus (MERS CoV) infection at a coronavirus referral center in the Kingdom of Saudi Arabia. Issue 1 (December 2016) - Al Ghamdi, Mohammed; Alghamdi, Khalid; Ghandoora, Yasmeen; Alzahrani, Ameera; Salah, Fatmah; Alsulami, Abdulmoatani; Bawayan, Mayada; Vaidya, Dhananjay; Perl, Trish; Sood, Geeta
Abstract Background Middle Eastern Respiratory Syndrome coronavirus (MERS-CoV) is a poorly understood disease with no known treatments. We describe the clinical features and treatment outcomes of patients with laboratory confirmed MERS-CoV at a regional referral center in the Kingdom of Saudi Arabia. Methods In 2014, a retrospective chart review was performed on patients with a laboratory confirmed diagnosis of MERS-CoV to determine clinical and treatment characteristics associated with death. Confounding was evaluated and a multivariate logistic regression was performed to assess the independent effect of treatments administered. Results Fifty-one patients had an overall mortality of 37 %. Most patients were male (78 %) with a mean age of 54 years. Almost a quarter of the patients were healthcare workers (23.5 %) and 41 % had a known exposure to another person with MERS-CoV. Survival was associated with male gender, working as a healthcare worker, history of hypertension, vomiting on admission, elevated respiratory rate, abnormal lung exam, elevated alanine transaminase (ALT), clearance of MERS-CoV on repeat PCR polymerase chain reaction (PCR) testing, and mycophenolate mofetil treatment. Survival was reduced in the presence of coronary artery disease, hypotension, hypoxemia, CXR (chest X-ray) abnormalities, leukocytosis, creatinine >1 · 5 mg/dL, thrombocytopenia, anemia, and renal failure. In a multivariate analysis of treatments administered, severity of illness was the greatest predictor of reduced survival. Conclusions Care for patients with MERS-CoV remains a challenge. In this retrospective cohort, interferon beta and mycophenolate mofetil treatment were predictors of increased survival in the univariate analysis. Severity of illness was the greatest predictor of reduced survival in the multivariate analysis. Larger randomized trials are needed to better evaluate the efficacy of these treatment regimens for MERS-CoV.